The role of melanocortin 1 receptor on melanogenesis pathway in skin color differentiation of red tilapia - Lan-mei Wang (Elsevier, 2022)
The skin color differentiation and variation are the main problems limiting the development of red tilapia commercial culture. The specific function and regulation mechanism of mc1r gene in fish pigmentation are still poorly understood. In this study, we investigated the mc1r sequence characteristics, expression profiles, localization and melanocortins (MSH)-mc1r role on melanogenesis pathway of red tilapia. The mc1r ORF of red tilapia is1056 bp, corresponding to 351 amino acid, which belongs to a family of G-protein-coupled receptors. Quantitative real-time PCR demonstrated that mc1r mRNA was mainly expressed in the brain and dorsal skin tissues of PB (pink with scattered black spots) fish. The mc1r gene was found to be expressed during early development stages of red tilapia. The mc1r mRNA expressions were high in the 48 h post-hatching (48hph), 24hph and cleavage stages. Immunofluorescence analysis revealed that Mc1r was concentrated mainly in the cytoplasm and intercellular substance of skin epidermis. Injection with caudal vein of ɑ-MSH at 2.5 mg g−1 resulted in significantly higher tyrosinase activity and melanin level in the dorsal and ventral skin of red tilapia. The expression of mc1r and tyr mRNA in the skin of red tilapia increased after ɑ-MSH injection. These results suggested that mc1r plays an important role in fish melanogenesis pathway through binding to α-MSH.